Standardized ileal amino acid digestibility of expeller-extracted canola meal subjected to different processing conditions for starter and grower broiler chickens. (17th March 2015) - Toghyani, M.; Rodgers, N.; Iji, P. A.; Swick, R. A.
Abstract : Six expeller-extracted canola meal (ECM) samples produced under different seed conditioning temperatures (90, 95, or 100°C) and screw torques in the second press (low or high) were evaluated in a 3 × 2 factorial arrangement of treatments to determine the effect of processing on standardized ileal amino acid digestibility (SID) in 10 and 24-day-old broilers. A nitrogen-free diet was fed to determine ileal endogenous amino acid flow. Each diet was fed for 5 d to 6 replicate cages of 10 or 7 chicks, and ileal samples were collected at 10 and 24 d, respectively. The endogenous flow (mg/kg DM intake) of CP and all amino acids except Cys decreased ( P  < 0.01) with age. Conditioning temperature by screw torque interactions were detected ( P  < 0.05) for apparent ileal digestibility (AID) of CP, Arg, Ile, Lys, Phe, Thr, Ala, Asp, Glu, Pro, and Ser at d 10, and the same trend was observed at d 24 except for Ile, Phe, Ala, and Pro ( P  > 0.05). Meals processed under medium conditioning temperature (95°C) at either low or high screw torque had the greatest ( P  < 0.05) AID of CP and total amino acids. The SID values followed a similar pattern as AID at both ages. When corrected for endogenous losses, the average AID of total amino acids improved approximately 3.5 and 2.0 units, at 10 and 24 d, respectively. The AID and SID values increased ( P  < 0.05) with age for most AA, but the effect of age was not consistent between ECMs. A negative correlation was detected between NDF and neutral detergent-insoluble nitrogen (NDIN) content of the meals and SID values of Lys at d 24 (r = −0.79, r = −0.76; P  = 0.001, respectively). Processing conditions affected CP and amino acid digestibility, likely because of alterations to the chemical composition of ECM and formation of indigestible complexes of amino acids with fiber. The AID and SID values increased with age independent of meal processing conditions.